Diversity, phylogeny and intraspecific variability of Paradiplozoon species (Monogenea: Diplozoidae) parasitizing endemic cyprinoids in the Middle East - Nejat, Farshad; Benovics, Michal; Řehulková, Eva; Vukić, Jasna; Šanda, Radek; Kaya, Cüneyt; Tarkan, Ali Serhan; Abdoli, Asghar; Aksu, Sadi; Šimková, Andrea (Parasitology, 2023)
Diplozoidae are common monogenean ectoparasites of cyprinoid fish, with the genus Paradiplozoon being the most diversified. Despite recent studies on Diplozoidae from Europe, Africa and Asia, the diversity, distribution and phylogeny of this parasite group appears to be still underestimated in the Middle East. The objective of this study was to investigate the diversity, endemism and host specificity of diplozoids parasitizing cyprinoid fish from the Middle East, considering this region as an important historical interchange of fish fauna, and to elucidate the phylogenetic position of Middle Eastern Paradiplozoon species within Diplozoidae. Four Paradiplozoon species were collected from 48 out of 94 investigated cyprinoid species. Three known species, Paradiplozoon homoion, Paradiplozoon bliccae and Paradiplozoon bingolensis, were recorded on new cyprinoid host species, and a new species, Paradiplozoon koubkovae n. sp., was recorded on Luciobarbus capito and Capoeta capoeta from the Caspian Sea basin in Iran and Turkey. Paradiplozoon bliccae, exhibiting a wide host range in the Middle East, expressed both morphological and genetic intraspecific variabilities. The four Paradiplozoon species collected in the Middle East were placed in divergent clades, showing the rich evolutionary history of diplozoid parasites in the Middle East. Our study also revealed that two lineages of African diplozoids have a Middle Eastern origin. We stress the importance of applying an integrative approach combining morphological, ecological and molecular methods to reveal the real diversity of diplozoids.
Keywords: host specificity; Turecko; Animals; Turkey; biologická evoluce; parasite fauna; zvířata; Biological Evolution; Cyprinoidei; evolutionary history; Phylogeny; fylogeneze; Cyprinidae; phylogeography; Trematoda